(untitled) (International Journal of Renewable, Green, and Sustainable Energy, 2025)
This study investigates the impact of various catalysts on bio-oil production from castor cake using the hydrothermal liquefaction (HTL) process. Castor cake, a non-edible agricultural residue, serves as a promising biomass feedstock for sustainable fuel generation. The experiments were conducted under subcritical water conditions, with different heterogeneous and homogeneous catalysts to evaluate their effects on bio-oil yield and composition. The presence of catalysts significantly influenced the deoxygenation and cracking reactions, leading to variations in the physicochemical properties of the resulting bio-oil. Catalysts such as Na₂CO₃ and ZnCl₂ demonstrated enhanced bio-oil yields and favorable hydrocarbon profiles. Gas chromatography–mass spectrometry (GC-MS) and elemental analysis revealed improved energy content and reduced oxygen content in catalyst-assisted runs. These findings highlight the critical role of catalytic selection in optimizing bio-oil quality and yield, supporting the advancement of sustainable biofuel production technologies.